2005
DOI: 10.1002/ijc.21490
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of the SEC31L1 and ALK genes in an inflammatory myofibroblastic tumor

Abstract: Inflammatory myofibroblastic tumor (IMT) is a neoplasm composed of myofibroblastic spindle cells and infiltrating inflammatory cells. Cytogenetic analyses have revealed that a subgroup of IMT, in particular among children and young adults, harbors clonal chromosomal rearrangements involving chromosome band 2p23. Further, molecular genetic studies have shown that these rearrangements target the ALK gene, serving as the 3 0 -partner in fusion genes with various translocation partners. In the present study, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(67 citation statements)
references
References 23 publications
(35 reference statements)
1
65
0
1
Order By: Relevance
“…The molecular results were validated by metaphase FISH with fosmid probes flanking the SEC31A gene that confirmed a cryptic rearrangement of SEC31A associated with an insertion of its 5' end in the vicinity of the 3' end of ALK at 3q27, and duplication of this region on add (20) (Figure 1B; Online Supplementary Table S1). The latter aberration was additionally proved by FISH with probes covering the 5' end of SEC31A (WI2-2194A15 in red) and the 3' end of ALK (P1 clone 1111H1 in green) ( Figure 1B; Online Supplementary Table S1).…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…The molecular results were validated by metaphase FISH with fosmid probes flanking the SEC31A gene that confirmed a cryptic rearrangement of SEC31A associated with an insertion of its 5' end in the vicinity of the 3' end of ALK at 3q27, and duplication of this region on add (20) (Figure 1B; Online Supplementary Table S1). The latter aberration was additionally proved by FISH with probes covering the 5' end of SEC31A (WI2-2194A15 in red) and the 3' end of ALK (P1 clone 1111H1 in green) ( Figure 1B; Online Supplementary Table S1).…”
Section: Resultsmentioning
confidence: 78%
“…Remarkably, similar complex aberrations were detected in a case of IMT in which the SEC31A-ALK fusion was originally identified. 20 Whether another case of ALK + LBCL with a cryptic insertion of the 3' end of ALK at 4q22-24 reported by Stachurski et al, 21 targets SEC31A remains to be clarified. The duplication of the ALK fusion gene found in case 1 has been recurrently reported in ALK-positive lymphoma.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…4,5,7,9,[20][21][22][23][24][25][29][30][31][32] Cytogenetic and molecular analyses have demonstrated a number of ALK fusion gene partners, including RANBP2-ALK, TPM3-ALK, TPM4-ALK, CLTCALK, CARS-ALK and SEC31L1-ALK. 5,9,21,25,29,31 In the present study, ALK rearrangements were identified in 14 of 21 cases of inflammatory myofibroblastic tumor of the urinary bladder.…”
Section: Utility Of Alk-1 Protein Expressionmentioning
confidence: 99%
“…Rearrangements of ALK with various gene partners have been identified in inflammatory myofibroblastic tumor from a number of anatomic sites. [20][21][22][23][24] Each rearrangement is believed to result in the creation of novel gene fusions and subsequently leads to aberrant ALK activation. In the urinary bladder, a few series and case studies have reported cases of inflammatory myofibroblastic tumor exhibiting ALK rearrangements.…”
mentioning
confidence: 99%